The Economic, Social and Psychological Effects of Obstetric Urinary Fistula on The Patients Seen at Abbo Center- Khartoum Teaching Hospital (Sudan) 2016. - Ahmed, Lujain Mardi Mohammed; Zaki, Asim Zaki Mohammed (مجلة الجزيرة للعلوم الصحية; مجلد 13 عدد 2 (2017), 2017)
Introduction: I chose the problem of obstetric urinary fistula [OUF] because it is a common preventable affliction in Sudan which needs to be seriously attended to. OUF is an abnormal communication between the ureter, bladder or urethra with the uterus cervix or vagina (mostly between the bladder and the vagina)[1]. Most often it develops when the presenting fetal part fails to pass smoothly through the pelvis or by surgical intervention by obstetric forceps. The majority of the cases are attributed to prolonged complicated labour due to inaccessibility of adequate and immediate obstetric health care. Victims often live an unworthy life. Many of them have been abandoned, rejected or divorced by their husbands and became ostracized by families and societies because of their repulsive smell and inability to engage in sexual activity or bear children. Victims suffer both psychological and social consequences. Many of them find it difficult to engage in any worthwhile financial activity. Objective: To know the social, economic and psychological impact of OUF on the females suffering from continuous vaginal urine leakage seen at Abbo Center Khartoum Teaching Hospital Sudan (2016). Methods: cross sectional hospital based study was done on all females with OUF seen at Abbo,s Center during October and November (2016), using specially designed computer friendly self constructed data sheet (questionnaire) . Data analysed using SPSS version 22. Results: the study was done on 30 OUF patients of whom 16 (55.2%) were primiparae.7 (23.33%) were married at age 14 or less. Twenty one (68.8%) of the patient’s incomes were decreased due to loss of jobs. Nine (28.6%) of husband’s incomes decreased after their wives developed OUF. Of those ..(62.5%) lost their jobs as they traveled with their wives seeking treatment. A mean of 19.45± 12.69 million Sudanese pound spent by each patient on treatment. One patient spent more than 50 million pounds (at that time) on traetment. Ten (36%) were either separated or divorced, 18 (61.5%) of them were abandoned by their husbands. Only 2 (6.60%) husbands chose to stay with their wives. Many patients suffered from various types of personality disorders ranging from the effect of loneliness and degradation in half of them 15 (50%), embarrassment in 20 (66.7%) because of their offensive odors, 16 (53.3%) feeling devalued or 17 ( 56.7%) hurt by others because of their smell. Lastly and most importantly suffered situational depression. Of the 30 patient investigated 11 did not show any evidence of depression. The remaining patients 19 (63.33%) suffered various ranges of depression: 3 (10%) of them had mild mood disturbance, one was border-line clinical depression, 8 (26.70%) had moderate depression, 5 (16.70 %) had severe depression and 2 (6.7%) developed extreme type of depression according to Becks Inventory Scale of depression. The sexual intimacy of more than half 19 (63.3%) of all participants were affected.Loss of their babies, secondary infertility and inability to work added a lot to the patients suffering ,social isolation, depression and grief. Furthermore the failure to close the OUF and insufficient support by health providers added more to the patients suffering. Happily 25 (82.8%) were hopeful of successful treatment in the future. Conclusions and recommendations: OUF leaves a woman physically, emotionally, financially and socially traumatized. All the study population suffered various types and degrees of personality disorders especially when they lost their babies, abandoned by their husband or inadequately supported by the relatives, friends or neighbors. This was made worse by the financial constraints and additional expenditure on treatment .Lack of support not only by the husbands, families and society will be the hardest consequence to withstand psychologically.Increasing the awareness of women about the importance of antinatal care is vital. Although the OUF is preventable, it is only possible if good maternal health services and well skilled care during pregnancy and childbirth are available. Social, economic and psychological support  are mostly needed for proper management.